Pengaruh Praktik Environment, Social, Governance (ESG) terhadap Nilai Perusahaan dengan Peran Moderasi Top Management Team (TMT) Diversity - Syifa Muhila Azra Aisyah,; Idrianita Anis, (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the effect of Environment, Social, and Governance (ESG) practices on firm value with the moderating role of Top Management Team (TMT) Diversity. This research uses secondary data obtained from annual reports and sustainability reports published on the Indonesia Stock Exchange and the official websites of the companies. The sampling technique was purposive sampling with a total of 30 companies in the industrial sector. The data analysis methods used were descriptive analysis and hypothesis testing. The results of the study show that only ESG practices and Top Management Team Age Diversity have a significant effect on firm value. Meanwhile, Top Management Team Gender Diversity, the interaction between Top Management Team Age Diversity and ESG, as well as the interaction between Top Management Team Gender Diversity and ESG, do not have a significant effect on firm value.